2017
DOI: 10.1159/000471800
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of Subungual Exostosis: A Retrospective Study of 10 Patients

Abstract: Introduction: Subungual exostosis (SE), the most common nail tumor of young adults, is a benign bony proliferation of the distal phalanx occurring beneath the nail. Misdiagnosis or late diagnosis frequently occurs and no dermoscopy features of this tumor were previously outlined. Material and Methods: To describe the dermoscopic appearance of SE, 10 patients with radiologically and histologically confirmed SE were retrospectively retrieved from our tertiary referral centers. Data regarding age, gender, time to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 6 publications
1
25
0
1
Order By: Relevance
“…In the pediatric series of Letts et al [3], one-third of the locations spared the irst toe. The 2 children aged 6 in the Picollo et al series had a irst ray unharmed [4]. Finally, three of our ive cases were on the 2nd or 3rd toe.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In the pediatric series of Letts et al [3], one-third of the locations spared the irst toe. The 2 children aged 6 in the Picollo et al series had a irst ray unharmed [4]. Finally, three of our ive cases were on the 2nd or 3rd toe.…”
Section: Discussionmentioning
confidence: 56%
“…Very few series have reported pediatric cases during the irst decade [3]. In the work of Piccolo et al, 2 patients were under 10 years of age [4]. Other authors have reported sporadic cases [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographically, the lesion is approximately 1 cm in diameter and projects from the dorsal or dorsomedial aspect of the distal portion of a terminal phalanx. It is composed of mature trabecular bone with attachment to the phalanx; the free end is flat, cupped and smooth, or irregular [ 9 ]. There is a large radiolucent cartilaginous cap [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a large radiolucent cartilaginous cap [ 3 ]. There is no cortical disruption or other abnormality of the distal phalanx [ 9 ]. Dermoscopy could be another useful technique, involved in the diagnostic process, although X-ray examination and histopathology are mandatory for the diagnosis [10].…”
Section: Discussionmentioning
confidence: 99%